Fatal Disseminated Toxoplasma gondii Infection in a Captive Harbour Porpoise (Phocoena phocoena). Issue 4 (November 2015) - Herder, V.; van de Velde, N.; Højer Kristensen, J.; van Elk, C.; Peters, M.; Kilwinski, J.; Schares, G.; Siebert, U.; Wohlsein, P.
Summary: A 7-year-old female harbour porpoise ( Phocoena phocoena ), born and held in captivity, suffered from reduced consciousness, imprecise and circling swimming movements and long phases of immobility over a period of 3 weeks. The animal died during treatment in a Danish open sea facility. Pathological examination revealed multifocal pyogranulomatous to necrotizing meningoencephalomyelitis, ganglioneuritis, plexus chorioiditis, myocarditis, hepatitis and adrenalitis with few intralesional protozoal tachyzoites and bradyzoites within cysts. Immunohistochemistry was positive for Toxoplasma gondii antigen within the lesions. Using polymerase chain reaction (PCR), the presence of T. gondii- specific genome fragments was confirmed. A multilocus PCR-restriction fragment length polymorphism analysis using nine unlinked marker regions (nSAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1 and Apico) resulted in the identification of T. gondii type II (variant Apico Type I), which is the T. gondii genotype dominating in Germany. This is the first description of disseminated fatal toxoplasmosis in a captive harbour porpoise that lived in an open sea basin. Surface water contaminated with toxoplasma oocysts is regarded as the most likely source of infection.